2011
DOI: 10.1002/jat.1746
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of common urinary biomarkers for hepatotoxicity induced by carbon tetrachloride, acetaminophen and methotrexate by mass spectrometry‐based metabolomics

Abstract: Liver toxicity represents an important healthcare issue because it causes significant morbidity and mortality and can be difficult to predict before symptoms appear owing to drug therapy or exposure to toxicants. Using metabolomic techniques, we discovered common biomarkers for the prediction of hepatotoxicity in rat urine using mass spectrometry. For this purpose, liver toxicity was induced by 5 days of oral administration of carbon tetrachloride (1 ml kg(-1) per day), acetaminophen (1000 mg kg(-1) per day) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…Results obtained from pervious study has been well supported our result that revealed elevation in liver enzymes level, who have demonstrated that MTX causes hepatotoxicity. [25][26][27] All these changes in the liver function tests in MTX -treated animals were considered the major evidences of the hepatoxicity of MTX. The present study showed oral administration of LOE significantly lowered the MTX induced serum levels ALT, AST and ALP as hepatic enzyme markers (Table1).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from pervious study has been well supported our result that revealed elevation in liver enzymes level, who have demonstrated that MTX causes hepatotoxicity. [25][26][27] All these changes in the liver function tests in MTX -treated animals were considered the major evidences of the hepatoxicity of MTX. The present study showed oral administration of LOE significantly lowered the MTX induced serum levels ALT, AST and ALP as hepatic enzyme markers (Table1).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the evaluation of renal function relies on the measurement of blood urea nitrogen and serum [145,146] creatinine, both of which exhibit relatively low sensitivity for the detection of renal damage. Therefore, it is important to identify new, sensitive and reliable renal toxicity biomarkers.…”
Section: Transcriptomics Examplementioning
confidence: 99%
“…Thus, the significantly changed endogenous metabolites were regarded as biomarkers for monitoring different diseases (Beger et al, 2010a). Recently, some metabonomics studies have been done to discover novel biomarkers for druginduced liver and kidney injuries (Boudonck et al, 2009;Kumar et al, 2012;Ma et al, 2010aMa et al, , 2010bWeiss and Kim 2011;Yang et al, 2012). According to the reported studies (Chan et al, 2008;Geenen et al, 2011;Kumar et al, 2012;Lenz et al, 2004;Uehara et al, 2014;Xu et al, 2011;Zhang et al, 2014;Zhao et al, 2012), several potential hepato-nephrotoxicity biomarkers come up, such as cholic acid (CA), taurine (TA), 5-oxoproline (5-OP), hippuric acid (HIP), uric acid (UA), 3-indoxyl sulfate (3-IS) and kynurenic acid (KA).…”
Section: Introductionmentioning
confidence: 97%